Harf Ma'ani's Distinction and Its Application in Arabic-Indonesian Translation - Sulthon Farhan Tsani; Ikhwanul Fitra Isman; Farrel Arfiko Ferdiansyah (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
This article explain the influence of